Asymmetric Truncated Hankel Operators: Rank One, Matrix Representation. (6th September 2021) - Rahmani, Firdaws; Lu, Yufeng; Li, Ran
Abstract : Asymmetric truncated Hankel operators are the natural generalization of truncated Hankel operators. In this paper, we determine all rank one operators of this class. We explore these operators on finite-dimensional model spaces, in particular, their matrix representation. We also give their matrix representation and the one for asymmetric truncated Toeplitz operators in the case of model spaces associated to interpolating Blaschke products.